Catalyzing policy action to address antimicrobial resistance: Next steps for global governance - Anthony D. So (South Centre, 2024)
The United Nations General Assembly has taken up Antimicrobial Resistance (AMR) twice in the past decade, but the follow-through on commitments and financing of both Global and National Action Plans on AMR have lagged considerably behind the policymaker pronouncements. The need to update the intersectoral approach to the Global Action Plan on Antimicrobial Resistance requires urgent attention if measurable progress is to be made in tackling this One Health challenge. This paper identifies where progress must pick up and outlines how intersectoral action might catalyze needed next steps.
Keywords: 300; Antimicrobial Resistance (AMR); Food and Agriculture Organization (FAO); Global Governance; Global Plan of Action (GPA); National Action Plans (NAPs); One Health; Quadripartite; United Nations (UN); United Nations Environment Programme (UNEP); United Nations General Assembly (UNGA); WHO Global Action Plan on AMR; World Health Organization (WHO); World Organisation for Animal Health (WOAH)